2005
DOI: 10.1111/j.1365-2141.2004.05340.x
|View full text |Cite
|
Sign up to set email alerts
|

Less than half of patients aged 65 years or under with myeloma proceed to transplantation: results of a two region population‐based survey*

Abstract: Summary In this population‐based survey covering two geographically distinct UK regions, we evaluated the number of myeloma patients aged ≤65 years who have not undergone transplantation. The combined data from both of these regions showed that 57% of age‐eligible patients were not transplanted. While early death and comorbidity accounted for nearly half of the non‐transplanted patients, we examined the other reasons for non‐transplantation within each region, assessed regional variations in reasons for non‐tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 6 publications
1
10
2
Order By: Relevance
“…Our results showed that a total of 212 patients with myeloma were discussed during the study period, giving an incidence of new myeloma cases of 42·8/million/year, which is similar to the rates quoted by Morris et al (2005) and confirms that a high proportion of new myeloma cases are being reported to the MDT. Of the 212 new myeloma cases discussed, 72 (34%) were aged <65 years and were considered eligible for high‐dose therapy at the initial MDT discussion.…”
Section: Reasons For Non‐transplantationsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results showed that a total of 212 patients with myeloma were discussed during the study period, giving an incidence of new myeloma cases of 42·8/million/year, which is similar to the rates quoted by Morris et al (2005) and confirms that a high proportion of new myeloma cases are being reported to the MDT. Of the 212 new myeloma cases discussed, 72 (34%) were aged <65 years and were considered eligible for high‐dose therapy at the initial MDT discussion.…”
Section: Reasons For Non‐transplantationsupporting
confidence: 88%
“…The proportion of patients proceeding to high-dose therapy therefore appears to be significantly greater than in the study by Morris et al (2005) (72% vs. 43%). Although we also found that co-morbidity was the commonest reason for non-transplantation (40%), the actual rate of co-morbid conditions within the myeloma patients aged <65 years was considerably lower at 11% compared with 19AE5% in the two-region study (Morris et al, 2005). This may possibly reflect a healthier population or, alternatively, earlier discussion with transplant physicians at the MDT meeting may have allowed some patients with co-morbidity to be accepted for high-dose therapy who might not otherwise have been referred.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…However, the prolonged use of alkylating agents such as melphalan is associated with an increased incidence of secondary malignancies, including myelodysplasia and acute leukaemia, and can also compromise subsequent collection of peripheral blood stem cells [4,5]. The introduction of high-dose therapy (HDT) with autologous SCT during the 1980s led again to a modest increase in OS of 3 – 5 years [610]; however, the proportion of patients proceeding to HDT and transplantation varies significantly (43 – 72%) dependent on age, co-morbidity, and failed stem cell mobilization [11]. Moreover, the majority of patients who undergo autologous SCT suffer from relapse.…”
Section: Medical Needmentioning
confidence: 99%
“…However, the prolonged use of alkylating agents such as melphalan is associated with an increased incidence of secondary malignancies, including myelodysplasia and acute leukaemia, and can also compromise subsequent collection of peripheral blood stem cells [4,5]. The introduction of high-dose therapy (HDT) with autologous SCT during the 1980s led again to a modest increase in OS of 3 -5 years [6][7][8][9][10]; however, the proportion of patients proceeding to HDT and transplantation varies significantly (43 -72%) dependent on age, co-morbidity, and failed stem cell mobilization [11]. Moreover, the majority of patients who undergo autologous SCT suffer from relapse.…”
Section: Medical Needmentioning
confidence: 99%